Staphylococcus aureus phagocytosis is affected by senescence - Robledo, Esteban; Benito Rodriguez, Paula Guadalupe; Vega, Israel Aníbal; Colombo, María Isabel; Aguilera, Milton Osmar (Frontiers in Aging, 2023)
Senescent cells accumulate in multicellular animals with aging, resulting in organ or tissue dysfunction. These alterations increase the incidence of a variety of illnesses, including infectious diseases, and, in certain instances, the severity of the same. In search of a rationale for this phenomenon, we focused on the endophagocytic pathway in senescent cells. We first described the endocytic vesicle populations at different stages of maturation in senescent cells using confocal microscopy. There was an increase in the number of vacuoles per cell, which was partially explained by an increase in cell size. No changes in vesicle maturation or degradation capacities were determined by microscopy or Western blot assays. Also, we studied the internalization of various endophagocytic cargoes in senescent cells and observed only a decrease in the intracellular recovery of bacteria. Afterwards, we studied the intracellular traffic of S. aureus, and observed no differences in the infection between control and senescent cells. We quantified the recovery of bacteria from control and senescent cells infected in the presence of several inhibitors of endophagosomal maturation, and no changes were observed. These results suggest that bacterial internalization is affected in senescent cells. Indeed, we confirmed this hypothesis by determining minor bacterial adherence and internalization by confocal microscopy. Furthermore, it is important to highlight that we found very similar results with cells from older animals, specifically BMDMs. This alteration in senescent cells enlightens the diminished bacterial clearance and may be a factor that increases the propensity to suffer severe infectious conditions in the elderly.